Spindle cell rhabdomyosarcoma of bone with FUS–TFCP2 fusion: confirmation of a very recently described rhabdomyosarcoma subtype. Issue 3 (29th June 2018) - Dashti, Nooshi K; Wehrs, Rebecca N; Thomas, Brittany C; Nair, Asha; Davila, Jaime; Buckner, Jan C; Martinez, Anthony P; Sukov, William R; Halling, Kevin C; Howe, Benjamin M; Folpe, Andrew L
Abstract : Aims: Rhabdomyosarcomas of bone are extremely rare, with fewer than 10 reported cases. A very rare subtype of spindle cell/sclerosing rhabdomyosarcoma harbouring a FUS–TFCP2 fusion and involving both soft tissue and bone locations has been reported very recently. We report only the fourth case of this unusual, clinically aggressive rhabdomyosarcoma. Material and results: A previously well 72‐year‐old male presented with a destructive lesion of the mandible. Morphological and immunohistochemical study of a needle biopsy and the subsequent resection showed a spindle cell rhabdomyosarcoma. RNA‐seq, RT–PCR and FISH confirmed the presence of the FUS–TFCP2 fusion. Conclusions: Spindle cell rhabdomyosarcomas carrying the FUS–TFCP2 fusion are very rare rhabdomyosarcoma variants with osseous predilection. The classification and differential diagnosis of this unusual molecular variant of spindle cell/sclerosing rhabdomyosarcoma are discussed.